CRIME AND CLUES DETECTIVE FORMULA IN ENOLA HOLMES 2022 FILM SCRPIT - Sulastri, Lilis Intan; Ruminda, Ruminda (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2024)
This research aims to analyze patterns of action and the contribution of crime elements and clues as part of the pattern of action in Enola Holmes 2022. The method used in this research is descriptive qualitative, with Cawelti's detective formula theory (1976) as the analytical framework. From the research results, researcher found some aspects of pattern of action which were grouped into several categories, namely detective introduction, crime and clues, investigation, announcement of solutions, explanation of solutions, and final resolution (denouement). The detective introduction category includes aspects that introduce the main character as an intelligent and independent young detective. In the crime and clues category, various elements were found that highlight how the crime is introduced and the clues are presented. The investigation category focuses on the search and information gathering process carried out by Enola. The solution announcement includes the moment where the solution to the mystery is revealed. The solution explanation details how Enola explains the steps taken to solve the case. The resolution category highlights how all the story elements tie together into one satisfying conclusion. This research shows that the Enola Holmes 2022 film uses pattern of action typical of the detective genre well to create an interesting story. Crimes and clues are essential in building the structure of the story, adding tension, and driving the plot forward.